(3QSGdI aj JMbjb GdMQcI aj GdeMhdGJs - (3eMeO Hf YHO GdaJGM GdHfcGHjfjs
(3ChdgG (B:s
(3bGd GdTjN aj GdaUd GdKGfj ef GdebGdI GdKGdKI ef WHjYjGJ GdTaG aj EHWGd chf GdMQcI s
(3BNQgG (B:s
(3aj GdUhQI agh cdGe BNQ dg bhI hdjS cdGefG Je cJH gPG GdQSGdI aj TgQ Pj GdMLg GdMQGe SfI (B1121(3g` s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdcJhQ MSjf Ydj eMahX (B- (3HZOGO (B(195) s
Keywords: (3GdJhMjO hGdedd hGdfMds